Conceito de dispositivos registradores de dados para veículos inteligentes - Barbosa, Henrique Coelho (2017)
The number of traffic accidents has increased recently. This can be justified by the higher number of vehicles on public roads, driver‟s negligence, poor road conditions, and other factors. In face of this, industries, academia, and the State has increased the interest in intelligent vehicles. They are an alternative to minimize traffic accidents. However, its insertion on public roads still requiring mechanisms to provide support to the State, once these vehicles are also susceptible to accidents and require an homologation/certification. Thus, a data recording device developed specifically for intelligent vehicles becomes a viable alternative to provide the necessary support in case of accidents. The present work focuses on discussing the importance of specifying this device, with a comparative study between the systems compounding the conventional road vehicles and the intelligent ones, addressing the different data produced. A concept of a standard data recording device for intelligent vehicles was also presented to validate this proposal. A discussion was held about its importance in understanding the accident causes involving intelligent vehicles and how this device could help us in the process of homologation/certification of the intelligent vehicles and its expandability to other sectors. Experiments in a simulated environment showed the viability of a data recording device in the analysis and reconstruction of scenarios with an operational fault.